Dydrogesterone use in recurrent pregnancy loss and luteal phase insufficiency: a knowledge, attitude, and practice survey amongst Indian obstetricians and gynaecologists - Tank, Jaydeep; Gupte, Sanjay; Mahapatra, Purna Chandra; Reddy, Jayanthi; Mittal, Pratima; Mukhopadhyay, Ashish Kumar; Vyas, Lila; Batra, Achla; Gupta, Mahesh; Tandulwadkar, Sunita; Chandra, Sunita; Bhat, Vidya; et al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Oral dydrogesterone is effective in treating reproductive disorders such as recurrent pregnancy loss (RPL) and is a better option than progesterone for luteal phase support (LPS) after in-vitro fertilization (IVF). This study aimed to assess the attitude, knowledge, and practice of obstetricians and gynecologists (ObGyns) across India towards the usage of dydrogesterone in RPL and LPS in real-life setting. Methods: A validated questionnaire-based survey was conducted among Indian ObGyns and results were expressed in percentages. Results: 393 ObGyns participated in the survey. 61.3% of ObGyns agreed RPL is the three consecutive pregnancy losses prior to 20 weeks from the last menstrual period. With the use of dydrogesterone in RPL patients, 82.6% of ObGyns found ˃40% of patients having successful pregnancy outcomes. 37.2% of ObGyns mentioned that dydrogesterone is useful in ongoing pregnancy rates while 33% reported benefits in the live birth rate. At the risk for preterm delivery before 34 gestational weeks, 57% of ObGyns see benefits of dydrogesterone. More than 95% of ObGyns observed benefits of dydrogesterone over micronized progesterone such as good efficacy, fewer side effects, better tolerability, and improved patient compliance. 51.9% of ObGyns reported that they used dydrogesterone in combination with progesterone in LPS. Conclusions: The present KAP survey highlights the observation, perception, and practicing behaviour of ObGyns on RPL and LPS. It also highlights the usage of dydrogesterone in aforesaid indications.